The Meaning of the Traditions of the Month of Ramadan in the Lives of The People of Lombok, NTB - Aulia Iswaratama (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research is a form of qualitative research that explains Ramadan rituals in Lombok. Qualitative research is research that produces descriptive data such as written words resulting from observing people's behavior. This research focuses on the traditions carried out by the people of Lombok, starting from welcoming the arrival of the holy month of Ramadan to traditions after celebrating Eid or Eid al-Fitr. These traditions have existed for a long time and are a heritage that is guarded and preserved and used as an activity or routine by the people of Lombok. Through this tradition, people hope to receive blessings and a form of gratitude from the community for being able to meet or fast during Ramadan.